PERBANDINGAN FAKTOR RISIKO DAN MANIFESTASI KLINIS HPV 16 DENGAN HPV 18 PADA PENDERITA KARSINOMA SERVIKS - Anavelda, Aura Putri; Putra, Andani Eka; Defrin, Defrin; Suharti, Netti; Antonius, Puja Agung; Elmatris, Elmatris (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: High-risk Human Papillomavirus (hrHPV) infection causes 99.7% of cervical carcinoma cases. Among the thirteen types of hrHPV, types 16 and 18 have a strong correlation with- cervical carcinoma. HPV 16 infection makes the immune system in the cervix hyporesponsive compared to HPV 18 infection. Objective: This study aims to compare the risk factors and clinical manifestations of HPV 16 with HPV 18 in cervical carcinoma patients. Method: This is an analytic study with a retrospective cohort approach using secondary data from the research of Dr. dr. Andani Eka Putra, M.Sc and dr. Syandrez Prima Putra which has been collected into a research master table. The sampling technique was non-probability sampling with convenience sampling on 38 respondents whose specimens were stored at the Central Laboratory of Diagnostics and Research on Infectious Diseases, Faculty of Medicine, Andalas University. Data analysis was carried out using Fisher's Exact test. Results: The results of statistical tests on the comparison of marriageable age between patients with HPV 16 and HPV 18 types showed a value of p = 0.038 (p <0.05). In this study, women who are > 45 years old, married early (<20 years), have a low level of education, work as housewives, and have a multiparity history are at high risk of cervical carcinoma. Patients with HPV 16 and 18 had risk factors and clinical manifestations were not much different (p>0.05). Conclusion: There is no significant comparison of the risk factors and clinical manifestations of HPV 16 with HPV 18 in patients with cervical carcinoma.